The structure of a long-period stacking phase in an Mg–Al–Y alloy studied by electron microscopy. Issue 24 (23rd August 2018) - Takeda, Mitsuhiro; Konno, Kazuya; Yasuhara, Akira; Hiraga, Kenji
ABSTRACT: A new phase with a 10H-type long-period stacking (LPS) structure was found in an Mg75 Al10 Y15 alloy annealed at 823 K. The LPS structure in the Mg75 Al10 Y15 alloy annealed at 823 K for 2 h has an ordered arrangement of L12 -type structural Al6 Y8 clusters on the two-dimensional plane parallel to the c -plane of hexagonal Mg lattice and a disordered arrangement along the c -axis, whereas a perfectly ordered structure along the c -axis, which has a period with two times of that of the 10H-type LPS structure, was established by annealing at 823 K for 24 h. The structural model of the ordered LPS phase is proposed by high-resolution images taken with a Cs-corrected scanning transmission electron microscope and also electron diffraction patterns.